Occurrence and Fate of Emerging Pollutants in Water Environment and Options for Their Removal - Vasilachi, Ionela; Asiminicesei, Dana; Fertu, Daniela; Gavrilescu, Maria (Water (Basel), 2021)
Emerging pollutants (EPs) are chemicals known to cause major impacts on the terrestrial, aquatic life and human health as a result of their chronic and acute toxicity. Although lots of studies on EPs behavior in the aquatic environment are currently available in literature, an urgent requirement exists to complete toxicological studies and develop and implement efficient and ecological methods for their removal. This paper raises some relevant problems related to water environment pollution with EPs, the risks they can generate for aquatic life and humans and opportunities to reduce the effects of pollution by EPs removal. Categories of emerging chemicals of concern in the environment, their sources, fate and impacts, with some examples are discussed. Organic UV filters are shortly presented as a relative new EPs category, with a focus on the need to develop extensive experimental studies on their environmental occurrence, fate and removal. Furthermore, sources for the aquatic environment resulting from discharging EPs directly into rivers from wastewater treatment plants are examined. The incidence of environmental and human health risks related to EPs is also considered. The removal of EPs from the environment as a solution to risk mitigation is addressed, with emphasis on several non-conventional processes involving biological removal of EPs. The paper provides a critical look at the current challenges posed by the presence of emerging pollutants in the aquatic environment, with critical comments and recommendations for further research to reduce the impact of EPs on water and human health and improve the performance of developed methods for their removal.